2020
DOI: 10.15826/umpa.2020.02.014
|View full text |Cite
|
Sign up to set email alerts
|

University Professors and the Digitalization of Education: On the Threshold of Force Majeure Transition to Studying Remotely

Abstract: Аннотация. В марте 2020 года российское образование в форс-мажорном Порядке перешло на удаленный режим работы вследствие угрозы распространения вируса Covid-19. В то же время дискуссии и деятельность по развитию онлайн-образования в России ведутся уже несколько лет. В статье на основе данных полуструктурированных интервью с преподавателями ведущих российских университетов рассматриваются вопросы, связанные с использованием академическими работниками цифровых технологий и отношением представителей высшей школы … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…However, as Abramov points out, high centralization and lack of university autonomy also tends to hinder the potential of universities for development due to the emphasis on administrative procedures and high level of bureaucracy which can replace universities' search for innovations, experiments and new solutions (Abramov et al., 2021 ). Particularly, Abramov et al ( 2020 ) indicated two trends, which occurred due to the shift to remote teaching and learning: from one hand, it led to the rival of academic autonomy due to academic self‐management, development of professional networks and community support. From the other hand, it enhanced the administrative control and digital bureaucratization in universities, which is perceived as a threat to academic autonomy.…”
Section: Russian Higher Education During the Pandemicmentioning
confidence: 99%
“…However, as Abramov points out, high centralization and lack of university autonomy also tends to hinder the potential of universities for development due to the emphasis on administrative procedures and high level of bureaucracy which can replace universities' search for innovations, experiments and new solutions (Abramov et al., 2021 ). Particularly, Abramov et al ( 2020 ) indicated two trends, which occurred due to the shift to remote teaching and learning: from one hand, it led to the rival of academic autonomy due to academic self‐management, development of professional networks and community support. From the other hand, it enhanced the administrative control and digital bureaucratization in universities, which is perceived as a threat to academic autonomy.…”
Section: Russian Higher Education During the Pandemicmentioning
confidence: 99%
“…Несмотря на растущую популярность платформ-интеграторов среди взрослого населения, анализ современных публикаций позволяет констатировать отсутствие исследований, направленных на изучение изменения динамики предложения программ непрерывного образования на данных ресурсах. Публикации, посвященные влиянию пандемии коронавирусной инфекции на процесс обучения, направлены на изучение готовности системы образования и её субъектов к экстренному переходу в онлайн (Abramov et al, 2020;Klyagin et al, 2020) и рассмотрению основных организационных трудностей из-за возникшей ситуации.…”
Section: дискуссионные вопросыunclassified
“…Пандемия коронавирусной инфекции (COVID-19), затронувшая все страны мира в начале 2020 года, и режим социального дистанцирования привели к настоящему буму в сфере онлайн-образования из-за перехода образовательных организаций на дистанционный формат обучения (Abramov et al, 2020). Онлайн-обучение для многих взрослых граждан стало сейчас единственным способом приобретения новых компетенций для сохранения и укрепления своих позиций на рынке труда.…”
Section: Introductionunclassified
“…On the other hand, for students' classroom performance during the epidemic, there are relevant data that show that students' class attendance was consistently high, even higher than in traditional classes, but attendance dropped significantly in the middle weeks of the due period [7] this is supported by a study by Zhang et al and others [5], who found that undergraduate students, compared to master's students' higher levels of online teaching engagement; also, the team found that postgraduate students were generally better at teaching in the digital classroom than undergraduate students by using a combined weighting-TOPSIS model to measure weights. This demonstrates that technology is not always the most important aspect of digital teaching and learning, but rather the people [8].…”
Section: Digital Teaching and Learning In Practice During The Pandemicmentioning
confidence: 99%